EGFR Activation Leads to Cell Death Independent of PI3K/AKT/mTOR in an AD293 Cell Line - Treda, Cezary; Popeda, Marta; Ksiazkiewicz, Magdalena; Grzela, Dawid P.; Walczak, Maciej P.; Banaszczyk, Mateusz; Peciak, Joanna; Stoczynska-Fidelus, Ewelina; Rieske, Piotr (PLOS ONE, 2016)
The Epidermal Growth Factor Receptor (EGFR) and its mutations contribute in various ways to tumorigenesis and biology of human cancers. They are associated with tumor proliferation, progression, drug resistance and the process of apoptosis. There are also reports that overexpression and activation of wild-type EGFR may lead to cell apoptosis. To study this phenomenon, we overexpressed in an AD293 cell line two most frequently observed forms of the EGFR receptor: wild-type and the constitutively active mutant–EGFR variant III (EGFRvIII). Then, we compared the effect of EGF stimulation on cell viability and downstream EGFR signaling. AD293 cells overexpressing wild-type EGFR, despite a significant proliferation increase in serum supplemented medium, underwent apoptosis after EGF stimulation in serum free conditions. EGFRvIII expressing cells, however, were unaffected by either serum starvation or EGF treatment. The effect of EGF was completely neutralized by tyrosine kinase inhibitors (TKIs), indicating the specificity of this observation. Moreover, apoptosis was not prevented by inhibiting EGFR downstream proteins (PI3K, AKT and mTOR). Here we showed another EGFR function, dependent on environmental factors, which could be employed in therapy and drug design. We also proposed a new tool for EGFR inhibitor analysis.